A study on stenting in coronary bifurcation lesions - S., Parameshwar; ., Rashmi; P. V., Dattatreya (International Journal of Research in Medical Sciences, 2017)
Background: Lesions at coronary bifurcations represent a challenging area in interventional cardiology. Treating bifurcation lesions involves weighing the risk of side-branch closure and the need for additional stent, sometimes requiring complex techniques. There are no specific guidelines established in choosing a one-stent versus a two-stent technique for a bifurcation lesion. The decision is highly dependent on its anatomic configuration and operator preference and expertise. Methods: Twenty patients of coronary artery bifurcation disease, most of them are double vessel disease with bifurcation coronary lesions planned for bifurcation stenting are included in the study. All the twenty patients’ risk factors, angiographic profile, and the technique used for bifurcation stenting are noted. Different stenting techniques are used for bifurcation stenting. Patients clinical follow up at three months, six months and at nine months done. Depending on the clinical symptoms patients are subjected for coronary angiogram. Results: Patients with complex stenting techniques (T stenting, SKS, & Crush) when compared to simple (provisional stenting) showed increased MACE during nine month follow up. Conclusions: The general consensus is that for bifurcation lesions without high risk features, the default approach of one stent PCI with provisional angioplasty plus stent is appropriate. For bifurcation lesions with high risk features, two stent techniques may be safer due to protection and treatment of the SB vessel. When coronary bifurcation lesions are treated with a systematic 2-stent technique results in higher rates of major adverse cardiovascular events on follow up at 9 months.